The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/fst.08119
|View full text |Cite
|
Sign up to set email alerts
|

Activity of polyphenoloxidase and peroxidase in non-dormant potato tubers treated with sprout suppressors

Abstract: Dne of the major problems affecting potatoes quality on stored is the susceptibility to enzymatic browning, which occurs mainly after wounds during the harvest, at postharvest handling and by aging, leading to the development of dark color compounds. Enzymatic browning is associated with the action of polyphenoloxidases (PPD) and peroxidases (PDD), which use phenolic compounds and oxygen as substrates. The products of these enzymes cause undesirable changes of color and flavor of processed potato products. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…1 and 2). These results were consistent with those reported for polyphenol oxidase and peroxidase of Loquat fruit [31] and PPO and POD of potato tubers [32].…”
Section: Resultssupporting
confidence: 93%
“…1 and 2). These results were consistent with those reported for polyphenol oxidase and peroxidase of Loquat fruit [31] and PPO and POD of potato tubers [32].…”
Section: Resultssupporting
confidence: 93%
“…Regardless of the cultivar and the storage time, the color of the sticks before frying was clear (Figure 3), without enzymatic browning due to the reaction of polyphenol oxidase (POD) with phenols (Paul et al, 2016). Studies by Santos et al (2020) found an increase in the enzymatic activity of polyphenol oxidase with the storage time and reduction with the use of sprouting inhibitors, eugenol and menthol for up to 40 days. However, visually there was no enzymatic browning due to the increase in the storage time and growth of the sprouts.…”
Section: Resultsmentioning
confidence: 99%
“…As for the potatoes, the optimum temperature for PPO activity has been initially determined at 40°C (Li et al., 2018). However, a recent study has shown that both PPO and POD exhibited their optimum activities between 30 and 35°C, and a substantial activity reduction occurred between 50 and 60°C (Santos et al., 2020). This is despite the fact that POD is known to exhibit considerable heat resistance and is commonly used as a quality indicator for thermal processes (Rojas et al., 2017).…”
Section: Anti‐browning Methodsmentioning
confidence: 99%